Critical Discourse Analysis of Meghan Markle’s Identity in the Interview with Oprah Winfrey in 2021 - Ban Asa’d Abood, Assistant Lecturer (lark, 2022)
The current paper deals with a critical discourse analysis of the underlying ideology of Duchess Meghan Markle in her conversation with Oprah Winfrey in 2021 in one of the most important royal interviews since princess Diana’s Panorama interview in 1995. The paper starts with theoretical information about the concepts of identity, ideology, race and critical discourse analysis (CDA). The researcher analyzes three selected extracts from this conversation by using van Dijk’s (2004) framework to investigate how Meghan Markle tried to justify her ideas and persuade the audience by utilizing subtle ideological discourse structures in her speech.